Analysis on Exchange of Information (EOI) to Increase the Quality of Investigation on Beneficial Owner Dispute (BO) According to Verdict of Tax Court from 2013 to 2015 in Directorate of Objection and Appeal - Rudi Hartasetiadi; Machfud Sidik (Ilomata International Journal of Tax and Accounting, 2019)
Based on the research of Taxpayer who has done a cross-jurisdiction transaction, known that taxpayers have done several transactions with Tax Heaven country corporation. One of the goals of the transaction is to take advantage of the gap on Tax Treaty /P3B to achieve treaty benefit. Tax auditing is a tool to ensure that the party who received the income in treaty partner countries is the Beneficial Owner (BO) thus there will be no misused of P3B/treaty abuse. Exchange of Information (EOI) is a tool for gaining information, evidence, and/or explanation to gain a conviction of who are truly received the benefit. Considering the importance of quality of investigation to appeal in Tax Court, it is interesting to review about the usage of Exchange of Information (EOI) to increase the quality of tax investigation of BO dispute, in this case, Directorate of Objection and Appeal. In arranging this research, researchers used a qualitative approach considering the focus of research is the usage of EOI on the investigation which has many factors and not monocausal means there is no one single cause from social reality. This research intends to know the use of EOI in increasing quality of tax auditing if it is reviewed from Tax Court verdict, supporting entities and the efforts which support the use of EOI in increasing the investigation of beneficial owner dispute. The result of this research explains that EOI usage to increase the quality of tax auditing of beneficial owner dispute has not been maximal or still low if it is assessed from the Tax Court verdict which DGT's percentage of losing verdict is higher than winning verdict. Factors that contributes the usage of EOI in increasing the quality of examination is human resource, which have good quality and quantity of examiner, competent database system and good obedience of taxpayers, good technique of examining, clear and not misinterpreted rules of BO and EOI, good cooperation between partner country, good coordination and support in internal unit of DJP. Meanwhile, entities that could obstruct usage of EOI in increasing investigation quality of beneficial owner dispute is the human resource, which means that investigation quality that has to be increased and quantity of the investigators that are not sufficient. Directorate General of Taxes not yet has competent database, low obedience of taxpayers, absence of rules about Investigation Technique about beneficial owner dispute, limited period of investigation, different interpretations from judges, inchoate and unclear information in EOI, answers of EOI request that has not fulfilled by cooperating countries and unclear and weak rules about beneficial owner